Microfinanza: analisi d’impatto di un programma in India (Microfinance: Impact Analysis of a Programme in India) - Tommaso Rondinella (Moneta e Credito, 2012)
Impact analysis of microfinance programmes is a useful tool both for improving the offered services and for guaranteeing donors that the money granted are used for programmes effective in poverty reduction. The present paper is constituted of two parts: the first is dedicated to impact analysis, the second to the empirical analysis on the field. The survey has been carried out using a tool able to give a clear indication of changes happened in recipients' life conditions and with the merit of being a low cost tool. Results show in what measure access to credit may change life conditions of the poorest driving to important increases in household income, savings, diversification of income generating activities and food consumption. Furthermore, an increase in female empowerment clearly dependent on the participation to microfinance programme is observed.